(Re)Considering the Pre-Burial Life of Grave Goods: Towards a Renewed Debate on Early Medieval Burial Chronology on the Continent - Kars, Mirjam (Medieval and Modern Matters, 2012)
Abstract The reduction of the length of chronological phases is still a major issue in the current chronological debate in early medieval archaeology on the continent. Short phases imply a rapid and steady change of grave goods assemblages and are thought to support the assumption that the dead were buried with their inalienable personal possessions. This article explores the premises that relate to short phases and the chronological method of seriation, which excludes social variables as essential components of the dating process. Various modes of object exchange and transmission are therefore the next discussion in this article. It is suggested that the wide variety of movables from graves were more often subject to prolonged circulation than generally assumed. The discussion of exchange and transmission shows that the chronological debate can be extended with a theoretical component that reflects on the role of the pre-burial life of objects which contributes to the understanding of chronological results. Abstract La diminution des durées en périodisation absolue est au coeur d’un débat sensible sur les chronologies continentales du haut Moyen Âge. De courtes périodes sous tendent des changements rapides et réguliers dans la composition des assemblages mobiliers, et confort l’idée que les défunts sont enterrés avec leurs biens personnels inaliénables. Cet article met en discussion les fondements d’une périodisation courte et les méthodes de sériation utilisée pour les établir. La sériation automatique souffre par ailleurs de l’absence de variables d’ordre social pourtant indispensable à une démarche de datation. Nous aborderons ensuite la variété des modes d’échange et de transmission des biens et suggérons qu’une large variété de mobiliers provenant des sépultures a souvent circulé bien plus longtemps que supposé. La considération des échanges et de la transmission impose d’élargir le débat chronologique à celle, théorique, du rôle des objets avant leur usage funéraire. Elle est indispensable à la compréhension des résultats des chronologies établies.